Implementation of Trademarks as Intellectual Property in Packaging - Maheni, MRR. Tiyas; Bangun, Dwi Agnes Natalia; Pramesti, Rachmadita Dwi (KnE Social Sciences, 2024)
Trademarks are intellectual property that needs to be protected. In some previous studies, more at the normative juridical level, no research has been able to examine in depth the application of brand element. This research is important considering the fact that the use of brands has strategic value in business competition. This study aims to describe the use of brand elements as intellectual property according to the Trademark Law and by its application in the field, namely on the product packaging The research method used is descriptive qualitative analysis by combining a normative juridical approach and analyzing the form and application of the brand on the packaging. The research stage begins by conducting a study of the Trademark Law, and then observing the form and application of the brand on the packaging of food and beverage products. The samples used in this qualitative study were 50 packages of various foods and beverages where each packaging had its registered trademark, so that it could be checked on the database of the Directorate General of Intellectual Property and also be observed on the selected packaging. The period of the data collection was June to November 2021. The results obtained indicated that according to the trademark law, the brand elements used can be either conventional or non-conventional brands. However, in its application, the majority of the brands attached to packaging are conventional brands in the form of a combination brand of several brand elements mentioned in the Trademark Law, namely a combination of elements of images, colors, logos, names, words, and numbers. Keywords: trademark law, brand elements, intellectual property, packaging